Optimalisasi Peran Perempuan dalam Hukum Islam: Kolaborasi Akademik Internasional Indonesia-Singapura. - Rahel, Muhammad; Masruha; Ainun Barakah; Nadia Hanim; Moh. Ishaq; Izzatun Maghfirah; M Halilurrahman; Fauziyah; Yusmita (LP3M IAIFA Kediri, 2025)
The imbalance in understanding regarding women's religious authority and its relevance in contemporary Islamic law remains a challenge in academic circles. A space for dialectics is needed to bridge theoretical and practical perspectives globally in order to strengthen women's intellectual position. This activity aims to optimize the academic community's understanding of women's strategic role in religious authority and the strengthening of Islamic law through collaboration between Indonesian legal clinicians and Singaporean academics. The strategy used is a public education method through an International Virtual Seminar (Webinar). The implementation stages included cross-border technical preparations, dissemination of materials by experts, and interactive problem-based discussion sessions. This activity successfully involved 91 participants consisting of lecturers, teachers, and students. Evaluation results through participatory observation in digital spaces (Zoom and WhatsApp Group) showed high enthusiasm with responsive discussions. The majority of participants (100%) stated that they had gained a comprehensive new understanding of women's religious authority from the perspective of Islamic law in Indonesia and Singapore. This community service program succeeded in creating international academic synergy that strengthens contemporary legal literacy and provides intellectual legitimacy for women's roles in the public sphere and religious authority.